The Other Ethical Approval: The Importance of Being “Islamic” - Ahmed, Abdul-Azim (Fieldwork in Religion, 2018)
The researcher, in carrying the name of the institution, is bound to an ethical standard of behaviour; standards which are maintained through ethical approval that researchers must obtain from their departments before conducting research. There exists another form of ethical approval a fieldworker must obtain, that of their research participants. This Other Ethical Approval is often related to access; a participant must consider the researcher to have integrity in order to allow them the privileged insight into their own lives and behaviours. The article outlines and explores this secondary ethical approval derived from the author’s experience of conducting research as a doctoral student. It is argued that being attentive and conscious of the ethical standards of the research field can only improve the quality and rigour of the research, and is increasingly important in spaces where access is not easily obtained. After outlining the research project, there follows a statement of ethics as the author encountered and negotiated it in the field. It is expressed through statements derived from Islamic sacred texts, structured in a similar way to statements of ethics produced by scholarly associations such as the American Anthropological Association. This reflexive account will be of value to researchers interested in British Muslim studies, as well as to scholars researching contemporary religious communities more generally, who need ethical approval from their research participants.